Fabrication and Study of Large-Area QHE Devices Based on Epitaxial Graphene; IEEE Transactions on Instrumentation and Measurement; Vol. 64, iss. 6 - Novikov S. A. Sergey Avtonomovich; Lebedeva N.; Pierz K.; Satrapinski A. (2015, 2015)
Title screen